The Impact of Lower Atmosphere Forecast Uncertainties on WACCM‐X Prediction of Ionosphere‐Thermosphere System During Geomagnetic Storms - Wonseok Lee; In‐Sun Song; Ja Soon Shim; Guiping Liu; Geonhwa Jee (Space Weather)
Abstract Impacts of lower atmosphere forecast uncertainties on the Ionosphere‐Thermosphere (IT) system are investigated using the Whole Atmosphere Community Climate Model with Thermosphere and Ionosphere eXtension (WACCM‐X) for April 2010 and March 2013 geomagnetic storms. For each storm, a specified‐dynamics simulation (analysis run) is carried out by constraining the model dynamics using reanalysis data. Results of the analysis runs are used as initial conditions for forecast runs initialized on 20, 10, 5, 2, and 1 day before the storm onset time. The forecast runs show that errors in TEC compared to the analysis run appear in the equatorial region within 1–2 days after forecast starts with differences of about 10%. These discrepancies gradually expand to high‐latitudes after 10 days. These errors in TECs could be due to the deviations in the semidiurnal (SW2) and non‐migrating (DE3) tides that also occur within 1–2 days after forecast starts. SW2 and DE3 tides could modify the E‐region wind driven dynamo at low latitudes, affecting the vertical plasma drift in the F‐region, leading to the forecast errors in TEC. The TEC forecast errors at high‐latitudes could be due to the change in the column integrated O/N2, associated with tidal wind variations and resultant delayed change in vertical motions. The SW2 and DE3 tides can be affected by uncertainties in winds in the mesosphere and lower thermosphere (MLT) in the mid‐to‐high latitudes. The MLT wind uncertainties are correlated with gravity wave drag (GWD), suggesting that the uncertainties in GWD can be one of the major sources of IT forecast errors.